Sosialisasi Hukum UU Nomor 23 Tahun 2004 Tentang Penghapusan Kekerasan dalam Rumah Tangga - Asyari, Fatimah; Maisyarah; Iwan, Iwan; Isnawati; Slamet, Amin; Kurniawan Pasaribu, Benhard (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Law Number 23 of 2004 concerning the Elimination of Domestic Violence (UU-PKDRT) is an important legal basis for protecting the rights of victims of domestic violence. However, its implementation still faces social barriers in the form of the perception that domestic violence is a private matter that should not be revealed in the public sphere. This condition results in low reporting rates and weak protection for victims, especially women. This community service activity aims to increase legal awareness of residents of Karang Mumus Village, Samarinda City, regarding the issue of domestic violence through a participatory and educational legal socialization approach. The method used is descriptive qualitative with active involvement of residents in discussions, delivery of legal materials, and case studies of domestic violence that occurred in the surrounding area. This activity involved various community elements such as PKK mothers, students, village officials, and local leaders. The results of the activity showed an increase in community understanding of the forms of domestic violence, reporting mechanisms, and the importance of social support for victims. In addition, this activity succeeded in eroding the stigma that reporting violence is an embarrassing act. This outreach not only provides citizens with legal information but also fosters the courage to speak out against injustice and fight for their basic rights. These findings underscore the importance of community-based legal education as a long-term strategy for building legal awareness, empowering women, and promoting more just and equitable social change.